Treatment of Simulated Oily Wastewater by Ultrafiltration and Nanofiltration Processes - Al-Alawy, Ahmed Faiq; Al-Ameri, Mohammed Kamil (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
A study in the treatment and reuse of oily wastewater generated from the process of fuel oil treatment of gas turbine power plant was performed. The feasibility of using hollow fiber ultrafiltration (UF) membrane and nanofiltration (NF) membrane type polyamide thin-film composite in a pilot plant was investigated. Three different variables: pressure (0.5, 1, 1.5 and 2 bars), oil content (10, 20, 30 and 40 ppm), and temperature (15, 20, 30 and 40 ᵒC) were employed in the UF process while TDS was kept constant at 150 ppm. Four different variables: pressure (2, 3, 4 and 5 bar), oil content (2.5, 5, 7.5 and 10 ppm), total dissolved solids (TDS) (100, 200,300 and 400 ppm), and temperature (15, 20, 30 and 40 ᵒC) were manipulated with the help of statistical method of Taguchi in the RO process. Analysis of variable (ANOVA) and optimum condition was investigated. The study shows that pressure has the greatest impact on the flux of UF process, while temperature and pressure have similar contribution on flux of NF process. The temperature seems to have the greatest effect on TDS rejection. It was noticed that more than 96% oil removal can be achieved with flux of 624 L/m2.hr by UF process and that the fouling mechanism of UF process follows the cake/gel layer filtration model. It was observed that 100% removal of oil content can be achieved along with 79% for the TDS rejection and flux of 65 L/m2.hr by NF process. The result shows fouling in NF process follows the cake filtration model. It was concluded that the observed values are within ±5% of that the predicted which reflects a strong representative model. The treated wastewater has the characteristics that it can be reused in the process to reduce the operating cost.